Supervisory support for subordinates’ use of information and communication technologies: development and preliminary validation of a scale in a Chinese context - Juncheng Zhang; Wendelien van Eerde; Fang Liu; Weiqi Chen (Humanities & Social Sciences Communications)
Abstract The pervasive use of information and communication technology (ICT) for work comes at a considerable cost to well-being. This study focuses on the critical role of supervisors and introduces the concept of supervisory ICT support, a construct designed to capture the supervisory dimension of ICT interventions aimed at enhancing employee well-being. Through a four-phase procedure, we developed and validated a scale to measure supervisory ICT support. Based on 38 items generated from literature reviews and in-depth interviews, we conducted two surveys and applied exploratory (n = 206) and confirmatory factor analysis (n = 560) to identify the factor structure, resulting in two 4-item subscales: ICT consideration and ICT updating. To assess criterion validity, we conducted a two-wave survey (n = 387), which also enabled stronger causal inferences. The findings show that supervisory ICT support is a multidimensional construct, with two subdimensions—ICT consideration and ICT updating—and that it is positively related to employees’ ICT control, perceived control of time, sense of learning, and sense of vitality. This research is the first to conceptualize and measure the supervisor’s role in providing ICT-specific support to mitigate the negative effects of work-related ICT use on employees’ well-being. It extends the leadership literature on technostress coping and offers a reliable and valid scale for measuring supervisory ICT support. Organizations are encouraged to position supervisors at the center of ICT interventions and equip them with the necessary skills to consider employees’ emotional responses to ICT use. This study has practical implications for enhancing employee well-being in digital work environments by fostering supervisor-driven ICT support.